FT-IR, Laser-Raman, UV-Vis, and NMR Spectroscopic Studies of Antidiabetic Molecule Nateglinide - Tuba Özdemir Öge (Journal of Spectroscopy)
The quantum chemical calculations and spectroscopic and theoretical characterizations of nateglinide molecule, a derivative of meglitinide and an oral antidiabetic drug, were performed using FT-IR, Laser-Raman, and NMR chemical shift and UV-Vis analysis methods. The other parameters including geometric structures, optimized geometry, vibrational frequencies, dipole moments, infrared and Raman intensities, and HOMO and LUMO energies of nateglinide molecules were studied using the density functional theory. In addition, the 13C and 1H NMRs were calculated using Gaussian 09 program with the DFT/B3LYP method at the 6-31G + (d, p) basis set. TD-DFT calculations were performed to examine the electronic transitions including orbital energies, absorption wavelengths, oscillator strengths, and excitation energies in methanol. The research was performed to provide detailed spectroscopic information of antidiabetic nateglinide molecule’s monomer conformations.